2017
DOI: 10.1536/ihj.16-255
|View full text |Cite
|
Sign up to set email alerts
|

Role of Right Ventricular Dysfunction and Diabetes Mellitus in N-terminal pro-B-type Natriuretic Peptide Response of Patients With Severe Mitral Regurgitation and Heart Failure After MitraClip

Abstract: SummaryMitraClip (MC) is an alternative therapeutic option for patients with severe mitral regurgitation (MR) who are at high surgical risk. Most candidates for MC have severe heart failure (HF) with increased N-terminal pro-B-type natriuretic peptide (NT-pro BNP) levels. We sought to clarify the response of NT-pro BNP after MC and to identify the determinants of NT-pro BNP nonresponders. Among 136 consecutive patients successfully treated with MC, we excluded 20 patients due to low baseline NT-pro BNP levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In this study, both diseases were identified as negative predictors of the functional improvement after MitraClip procedure. Consistent with our results, diabetes mellitus was found to be a determinant of NT-proBNP nonresponse after MitraClip implantation [43]. In a large MitraClip registry study, it was also an independent predictor of 1-year mortality [44].…”
Section: Impact Of Diabetes Mellitus Und Arterial Hypertension On the Outcome Of Mitraclip Implantationsupporting
confidence: 88%
“…In this study, both diseases were identified as negative predictors of the functional improvement after MitraClip procedure. Consistent with our results, diabetes mellitus was found to be a determinant of NT-proBNP nonresponse after MitraClip implantation [43]. In a large MitraClip registry study, it was also an independent predictor of 1-year mortality [44].…”
Section: Impact Of Diabetes Mellitus Und Arterial Hypertension On the Outcome Of Mitraclip Implantationsupporting
confidence: 88%
“…12) BNP is a biomarker for cardiac dysfunction. 13) It is secreted by the heart in response to excessive stretching of the heart muscle cells and is released as preproBNP, 14) which comprises the biologically active BNP and the inactive metabolite N-proBNP. Researchers have reported that serum NT-proBNP and cTnI increased after prolonged endurance exercise, which is in correspondence with the decline of cardiac contractility; 12,15) how- C: Quantitative analysis of LC3 II immunoreactivity in myocardium (n = 25visuals/group).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the field is still not settled due to contrary results in smaller samples [ 34 ]. Heterogeneous comorbidities might explain nonresponse of NT-proBNP after PMVR [ 35 ].…”
Section: Discussionmentioning
confidence: 99%